Insecticide-induced hormesis in an insecticide-resistant strain of the maize weevil, Sitophilus zeamais - Guedes, N. M. P.; Tolledo, J.; Corrêa, A. S.; Guedes, R. N. C. (Journal of Applied Entomology, 2010)
Sublethal responses to insecticides are frequently neglected in studies of insecticide resistance, although stimulatory effects associated with low doses of compounds toxic at higher doses, such as insecticides, have been recognized as a general toxicological phenomenon. Evidence for this biphasic dose–response relationship, or hormesis, was recognized as one of the potential causes underlying pest resurgence and secondary pest outbreaks. Hormesis has also potentially important implications for managing insecticide‐resistant populations of insect‐pest species, but evidence of its occurrence in such context is lacking and fitness parameters are seldom considered in these studies. Here, we reported the stimulatory effect of sublethal doses of the pyrethroid insecticide deltamethrin sprayed on maize grains infested with a pyrethroid‐resistant strain of the maize weevil (Sitophilus zeamais) (Coleoptera: Curculionidae). The parameters estimated from the fertility tables of resistant insects exposed to deltamethrin indicated a peak in the net reproductive rate at 0.05 ppm consequently leading to a peak in the intrinsic rate of population growth at this dose. The phenomenon is consistent with insecticide‐induced hormesis and its potential management implications are discussed.
Keywords: Maize weevil; Sitophilus zeamais